Diet-Mediated Dilated Cardiomyopathy in the Canine - Ada-Miette J. Thomas; Alison Ramser; Sami Dridi (Advances in Food Technology and Nutrition Sciences, 2023)
Dilated cardiomyopathy (DCM) is a disease of the heart muscle resulting in decreased myocardial function and is the second most common myopathy in canine. Previously, canine dilated cardiomyopathy was considered to be an inherited disease among large and giant breeds, however, recent reports suggest a possible link between certain grain-free diets and this condition. Several investigations into the incidence of this condition in relationship to grain-free diet consumption have been conducted in recent years. The most recent research shows a static overall trend in the incidence of DCM despite a five-fold increase in the sales of grain-free pet foods. Inadequate intake of protein, taurine, and specific sulfur-containing amino acids may have a potential role in the development of DCM, as these nutrients are crucial for cardiac muscle development and function. However, significant research remains to be done on the topic to discern any potential definitive causation.